2004
DOI: 10.1186/ar1196
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A consensus conference with representatives from academia, governmental agencies, and the pharmaceutical industry met and concluded that clinical trials designed to assess the efficacy and effectiveness of treatments for chronic pain should consider outcomes in six core domains: pain, physical functioning, emotional functioning, patient global ratings of satisfaction, negative health states and adverse events, and patient disposition. In addition, it was acknowledged that there are many secondary domains that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…58;228230 Given the synergy between pain and negative affect, this makes good logical sense: efficacious analgesic treatments that reduce the frequency and intensity of pain should have a beneficial effect on patients’ affective states and appropriate treatment of emotional distress should have a positive influence on the experience of pain 9;12;128;137 . Indeed, several randomized controlled trials in primary care settings have shown that antidepressant treatment in patients with comorbid chronic pain and mood disorders produces fairly rapid analgesic benefits that are anticipated by, and robustly correlated with, improvements in indices of psychosocial distress 127;193 .…”
Section: The Biopsychosocial Model Of Painmentioning
confidence: 99%
“…58;228230 Given the synergy between pain and negative affect, this makes good logical sense: efficacious analgesic treatments that reduce the frequency and intensity of pain should have a beneficial effect on patients’ affective states and appropriate treatment of emotional distress should have a positive influence on the experience of pain 9;12;128;137 . Indeed, several randomized controlled trials in primary care settings have shown that antidepressant treatment in patients with comorbid chronic pain and mood disorders produces fairly rapid analgesic benefits that are anticipated by, and robustly correlated with, improvements in indices of psychosocial distress 127;193 .…”
Section: The Biopsychosocial Model Of Painmentioning
confidence: 99%
“…Collectively, while instruments assessing depression, anxiety, and distress have most often appeared as outcome measures in the pain RCT literature [75;228230], emerging evidence suggests that pre-treatment phenotyping of these patient symptoms can have important predictive effects [82]. On the basis of a review of the literature of measures of emotional functioning used in phenotyping participants in analgesic trials, the Hospital Anxiety and Depression Scale (HADS) can be recommended as a core phenotyping measure for assessing general negative affect (see the background materials for IMMPACT-XVI at http://www.immpact.org/index.html).…”
Section: Phenotypic Domainsmentioning
confidence: 99%
“…It has been estimated that there might be more than 30 million people in USA with chronic or recurrent pain [35]. Also nearly half of Americans seeking treatment from a physician report pain as their primary symptom.…”
Section: Introductionmentioning
confidence: 99%
“…Also nearly half of Americans seeking treatment from a physician report pain as their primary symptom. The United States Bureau of the Census estimated the total cost for chronic pain to exceed $150 billion annually in year 1995–96 [35, 10]. Thus there has been a significant research effort in improving pain management over the years.…”
Section: Introductionmentioning
confidence: 99%